The Effect of Patient Safety Educational Program on Nurses' Patient Safety Culture and Patient Safety Indicators - Nasrin Hanifi; Zahra Yazdanshenas; Masoumeh Namadian; Nima Motamed (JMIR Publications, 2018)
The need to improve patient's safety is to change the patient's safety culture. This study was conducted to determine the effect of the patient safety education program on nurses' patient safety culture and patient safety indicators. This single-blind clinical trial was conducted in two cardiac medical wards that were randomly selected as research settings among the hospital teaching wards of the Zanjan city in Zanjan. Twenty-six nurses participated in this study under in the experimental and control groups. The experimental group received the educational program for two sessions, and the control group received a booklet about patient safety. The nurses' patient safety culture was assessed using the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire before and 3 months after intervention. The patient safety indicators were assessed 1400 times before and 3 months after intervention using a standard checklist by direct observation of all indicators (N = 100 for each). The results revealed that the patient safety educational program could improve some safety indicators, and overall perception of patient safety composite from safety culture, positively (P = 0.034). The patient safety indicators in pharmacological considerations (P =0.001), personal information considerations (P =0.001), and proper implementation of procedure considerations (P = 0.001) were significantly improved in the experimental group compared to the control group. It seems that changing the patient's safety culture using educational program requires more training courses.